γ-Secretase modulator resistance of an aggressive Alzheimer-causing presenilin mutant can be overcome in the heterozygous patient state by a set of advanced compounds - Johannes Trambauer; Rosa Maria Rodriguez Sarmiento; Holly J. Garringer; Katja Salbaum; Liliana D. Pedro; Dennis Crusius; Ruben Vidal; Bernardino Ghetti; Dominik Paquet; Karlheinz Baumann; Lothar Lindemann; Harald Steiner (Alzheimer’s Research & Therapy)
Abstract Background Amyloid-β peptide (Aβ) species of 42 or 43 amino acids in length (Aβ42/43) trigger Alzheimer´s disease (AD) and are produced in abnormal amounts by mutants of the γ-secretase subunit presenilin-1 (PS1), which represent the primary cause of familial AD (FAD). Lowering these peptides by γ-secretase modulators (GSMs) is increasingly considered a safe strategy to treat AD since these compounds do not affect the overall cleavage of γ-secretase substrates. GSMs were shown to modulate not only wild-type (WT) γ-secretase but also FAD mutants, expanding their potential use also to the familial form of the disease. Unlike most other FAD mutants, the very aggressive PS1 L166P mutant is largely resistant to GSMs. However, these data were mostly obtained from overexpression models, which mimic more the less relevant homozygous state rather than the heterozygous patient situation. Methods Mouse embryonic fibroblast and induced pluripotent stem cell-derived neuronal PS1 L166P knock-in (KI) cell models were treated with various GSMs and Aβ responses were assessed by immunoassays and/or gel-based analysis. Results We identified GSMs that lower Aβ42 and/or Aβ43 when PS1 L166P is heterozygous, as it is the case in affected patients, and could reduce the amount of pathogenic Aβ species towards WT levels. RO7019009 was the most potent of these compounds, reducing both pathogenic species and concomitantly increasing the short Aβ37 and Aβ38, of which the latter has been associated with delayed AD progression. Another effective compound, the structurally novel indole-type GSM RO5254601 specifically acts on the Aβ42 product line leading to a selective increase of the beneficial Aβ38. Interestingly, we further found that this class of GSMs can bind not only one, but both presenilin fragments suggesting that it targets γ-secretase at an unusual binding site. Conclusion Our data show that even highly refractory presenilin FAD mutants are in principle tractable with GSMs extending the possibilities for potential clinical studies in FAD with suitable GSM molecules.